Bölgesel kalkınma çerçevesinde yatırım teşviklerinin shift- share analizi - (:unkn) unknown (My University, 2011)
Bölgesel kalkınma bağlamında, bölgelerin yatırım teşviklerinden göreli olarak yeterli pay alabilme durumları kadar, güçlü sektörlerde teşvikler almaları da büyük önem taşır. Bölgelere verilen yatırım teşviklerinin sektörel dağılımındaki değişimler, zamanla önemli farklılıkları da yansıtabilir. Bu temelden hareketle, Türkiye 'de yatırım teşviklerinin bölgesel dağılımındaki değişimler bölgesel kalkınma çerçevesinde analiz edilmiştir. Çalışmada 2002-2009 dönemi için shift-share tekniği kullanılmıştır. Bölgelerin teşvik almada uzmanlaştıkları sektörler ve teşvik piyasasında paylarını artırma durumları incelenmiştir.

In the context of regional development, besides taking enough shares from investment subsidies relatively, taking the subsidies in the powerful sectors is also important. The changes in the sectoral distribution of investment subsidies given to regions can also show important differences in the course of time. On this basis, the changes in the regional distribution of investment subsidies in Turkey are analyzed in the framework of regional development. The shift-share technique is used in this paper for the period of 2002-2009. The sectors which the regions specialize in aking investment subsidies and also, the matter of increasing their shares in the market of investment subsidy are examined.
A shif-share analysis of investment subsidies in the framework of regional development
Keywords: İktisat; İşletme